Madrasah Ibtidaiyah: A Study of interest and Process Skills in Mathematics - Syaiful, Syaiful; Kamid, Kamid; Kurniawan, Dwi Agus; Rivani, Putri Ayu (Journal of Education Research and Evaluation, 2021)
Schools are places where education is carried out for the purpose of national education. However, not all schools can achieve the expected goals. Like a school that has a priority in certain subjects. One of them is Madrasah Tsanawiyah which dominates subjects with religion. So the importance of this research is aimed at knowing the differences and the relationship between the interests and skills of students at Madrasah Tsanawiyah 4, 5 and 7 Batang Hari in mathematics lessons with flat side space material. This study uses quantitative methods with associative and comparative types. The sampling technique used in this study used simple random sampling. From the results of the T test and the correlation obtained, there are significant differences and relationships between students' interests and skills in learning mathematics with flat side space material. In this case it is proven by a significant value < 0.05 .